Fabrication and performance evaluation of polymeric membrane using blood compatible hydroxyapatite for artificial kidney application. Issue 11 (11th July 2021) - Zaman, Shafiq Uz; Saif‐ur‐Rehman,; Zaman, Muhammad Khaliq U; Rafiq, Sikander; Arshad, Amber; Khurram, Muhammad Shahzad; Irfan, Muhammad; Saqib, Sidra; Muhammad, Nawshad; Irfan, Masooma; Sharif, Faiza; Bustam, Mohamad Azmi; et al.
Abstract: In the current study, a phase inversion scheme was employed to fabricate hydroxyapatite (HA)/polysulfone (PSF)‐based asymmetric membranes using a film applicator with water as a solvent and nonsolvent exchanging medium. Fourier Transform Infrared (FTIR) and X‐ray diffraction (XRD) spectroscopic studies were conducted to confirm the bonding chemistry and purity of filler. The inherent thick nature of PSF generated sponge‐like shape while the instantaneous demixing process produced finger‐like pore networks in HA/PSF‐based asymmetric membranes as exhibited by scanning electron microscope (SEM) micrographs. The FTIR spectra confirmed noncovalent weak attractions toward the polymer surface. The leaching ratio was evaluated to observe the dispersion behavior of HA filler in membrane composition. Hydrophilicity, pore profile, pure water permeation (PWP) flux, and molecular weight cutoff (MWCO) values of all formulated membranes were also calculated. Antifouling results revealed that HA modified PSF membranes exhibited 43% less adhesion of bovine serum albumin (BSA) together with >86% recovery of flux. Membrane composition showed 74% total resistance, out of which 60% was reversible resistance. Biocompatibility evaluation revealed that the modified membranes exhibited prothrombin time (PT), and thrombin time (TT) comparable with typical blood plasma, whereas proliferation of living cells over membrane surface proved its nontoxic behavior toward biomedical application. The urea and creatinine showed effective adsorption aptitude toward HA loaded PSF membranes. Abstract : In the current work, hydroxyapatite (HA) was blended with polymeric doped solution and different wt.% composition‐based asymmetric membranes were prepared through a phase inversion scheme using water as an exchanging medium and characterized through different analytical techniques. The impregnation of HA in polymer matrix resulted in membrane with improved biocompatibility, hydrophilicity, and terrific protein rejection characteristics and having high adsorption aptitude for urea and creatinine.